A trust-based authentication framework for security of WPAN using network slicing - Sazia Parvin; Amjad Gawanmeh; Sitalakshmi Venkatraman; Ali Alwadi; Jamal N. Al-Karaki; Paul D. Yoo (Institute of Advanced Engineering and Science, 2021)
New technologies bring along many challenges including security and privacy. Wireless personal area networks (WPANs) are characterized by limited energy resources and computing power that calls for lightweight security mechanisms in these networks as a mandatory requirement. In this paper, a lightweight trust-based framework for node authentication in WPAN is proposed. Our main objective is to minimise the effort in distinguishing valid requests of trustworthy nodes from invalid requests of malicious nodes that can result in network compromises. We achieve this through network slicing which divides the network into virtually primary and secondary networks. The proposed framework has three-fold benefits. First, it authenticates nodes’ requests based on a novel method of trust value calculation. Second, the framework maintains energy efficiency while authenticating nodes’ requests to access WPAN resources. Finally, the framework provides a solution for biasing problem that can arise due to unexpected behaviour of malicious users in WPANs. The framework efficacy is illustrated on a case study to shown how it can accurately capture trust relations among nodes while preventing malicious behavior.